IMPLEMENTASI SISTEM GADAI SAWAH DALAM PERSPEKTIF ISLAM - Vista Firda Sari (LPPM STAI DARUSSALAM LAMPUNG, 2021)
This study aims to describe and analyze the implementation of the Pawn Pawn System in the perspective of Islamic law. This research uses a qualitative approach. The data analysis is inductive in nature based on specific facts. The results of the study concluded that the practice of pawning carried out could be said to be not in accordance with Islamic law, if there were some of the pillars and conditions of the pledge (rahn) that had not been fulfilled, such as the absence of a time limit for repaying the debt by the pawnbroker (rahin) to the recipient of the pawn (rahn). murtahin). The use of pawned goods (marhun) as collateral by the recipient of the pawn (murtahin), cannot be tolerated anymore and cannot be justified according to Islamic law, because it contains an element of exploitation of people who are weak and are experiencing difficulties, because they are unable to repay their debts. In addition, the essence of the stipulation of pawning (rahn) as a mutual assistance contract is also blurred and lost, which grows instead of a materialistic attitude in social life. The benefits of this research are to find out the implementation of pawning fields from an Islamic perspective, whether it is appropriate or not and being a reference to the community whether the transactions made are appropriate or not.